2008
DOI: 10.1088/0022-3727/41/12/123001
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in single-asperity nanotribology

Abstract: As the size of electronic and mechanical devices shrinks to the nanometre regime, performance begins to be dominated by surface forces. For example, friction, wear and adhesion are known to be central challenges in the design of reliable micro-and nano-electromechanical systems (MEMS/NEMS). Because of the complexity of the physical and chemical mechanisms underlying atomic-level tribology, it is still not possible to accurately and reliably predict the response when two surfaces come into contact at the nanosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
367
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(374 citation statements)
references
References 329 publications
(523 reference statements)
6
367
1
Order By: Relevance
“…In 2004, Urbakh et al summarised experimental and theoretical contributions to the fundamental understanding of both wet and dry friction [2]. Szlufarska et al reviewed experimental and theoretical studies of wet and dry friction specifically in the area of nanotribology in 2008 [11]. In 2013, Vanossi et al [12] summarised advances in nanoscale to mesoscale modelling of wet and dry friction while and in the same year Dong et al [13] discussed NEMD studies of dry friction in the context of atomic force microscopy (AFM) experiments.…”
Section: The Modern Molecular Approach To Viscosity Proceeds Via the mentioning
confidence: 99%
“…In 2004, Urbakh et al summarised experimental and theoretical contributions to the fundamental understanding of both wet and dry friction [2]. Szlufarska et al reviewed experimental and theoretical studies of wet and dry friction specifically in the area of nanotribology in 2008 [11]. In 2013, Vanossi et al [12] summarised advances in nanoscale to mesoscale modelling of wet and dry friction while and in the same year Dong et al [13] discussed NEMD studies of dry friction in the context of atomic force microscopy (AFM) experiments.…”
Section: The Modern Molecular Approach To Viscosity Proceeds Via the mentioning
confidence: 99%
“…Before doing so, in order to get a better insight on the problem we will briefly describe some of the main properties of the system for a perfect lattice ͑⑀ =0͒. 4,6,[8][9][10][11][12][13] For this case, the main results are shown in Fig. 2͑a͒ where we present the friction force as a function of the corrugation potential amplitude U o at small velocity ͑v s =10 nm/ s͒.…”
Section: Surface Disorder Without Temperaturementioning
confidence: 99%
“…Furthermore, as the interaction between two surfaces involves complex interactions among many asperities, the atomic force microscopy is an exceptional tool to better understand friction at nanoscale level since it can be described essentially as a single asperity dragged along a surface. 4,8 Most theoretical efforts to describe the force friction microscopy experiments have focused on the behavior of defect free and perfect periodic surfaces with or without the inclusion of thermal effects. [9][10][11][12] However, the study of the effect of substrate disorder or defects on atomic friction is particularly important since atomically flat surfaces represent ideal models and disorder and defects of different kind are always present in nature.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this work is to unveil the origin of wear for nt Cu at the nanoscale, which is expected to advance our understanding of the atomic nature of tribological behavior of nanostructured materials. [13][14][15][16][17][18] Recent experimental tests and atomistic simulations have shown that the strength of nt Cu has a strong dependence on twin boundary spacing (TBS). [19][20][21] The strength of nt Cu first increases with decreasing TBS in a Hall-Petch manner.…”
Section: Introductionmentioning
confidence: 99%